(untitled) (Journal of Informatics and Mathematical Sciences, 2021)
In this work, the author introduces new generalization of Gegenbauer polynomials of one and two variables by considering new extended gamma function defined by MacDonald function. Certain properties of this new generalized Gegenbauer polynomials like integral formulas, Mellin transform, recurrence relationsand generating function are presented and investigated.